Assessment of knowledge and awareness of stroke among Arabic speaking adults: unveiling the current landscape in seven countries through the first international representative study - Malaeb, Diana; Mansour, Sara; Barakat, Muna; Cherri, Sarah; Kharaba, Zelal J.; Jirjees, Feras; Al Zayer, Reem; Eltayib, Eyman M.; Khidhair, Zeinab; AlObaidi, Hala; El Khatib, Sami; Alex, Ruth; et al. (Frontiers in Neurology, 2024)
IntroductionWhile several studies have examined stroke public knowledge and awareness in individual countries within the Middle East and North Africa (MENA) region, none have provided a comprehensive cross-country assessment.PurposeTo assess public stroke knowledge and awareness among Arabic-speaking adults in seven MENA countries and identify associated factors.Materials and methodsAn online cross-sectional survey was self-administered by the public population in Iraq, Lebanon, Sudan, Jordan, United Arab Emirates, Syria, and Saudi Arabia (April 2021–2023). Associations of stroke risk factors, early symptoms, and consequences with socio-demographics and medical history were analyzed using logistic regression models.ResultsOf 4,090 participants (58.3% females), 42.9% identified four out of five correct answers related to general stroke knowledge. Only 25.2% identified all stroke risk factors, 24.7% recognized all symptoms, and 37.5% knew all possible consequences. Results show consistent pattern of high identification for at least one risk factor and consequences across all countries (96.3 to 99.8% and 86.2 to 100%, respectively), with varying levels of early symptom identification (56.8 to 97.9%). Females were more likely to identify a stroke risk factor, symptom, and consequence compared to males (OR = 2.525, 2.474, and 2.302, respectively, p < 0.001). Employed, urban residents, and those with higher education demonstrated better stroke awareness.ConclusionThe sample showed variable levels of stroke knowledge among the public, underscoring the pressing need for targeted community initiatives, media campaigns, and educational interventions. These efforts are paramount for improving awareness, early detection, and timely response, especially in countries with lower levels of community stroke awareness.